EFEK MEDIASI KOMITMEN ORGANISASI ATAS PENGARUH CYBERLOAFING TERHADAP KINERJA KARYAWAN (Accounting Study Program, Universitas Ciputra Surabaya, 2022)
This study aims to examine the analysis of cyberloafing behavior on employee performance mediated by organizational commitment. This type of research is quantitative with procedures for data collection using a questionnaire method through a questionnaire. The sampling technique used is purposive sampling, namely sampling with criteria from the population. The sample of this study uses employees who work at PT Dinamika Megatama Citra who are domiciled in Mojokerto. The data analysis technique used is SEM-PLS by analyzing the data in two steps, namely the outer model and the inner model. The results of this study found that cyberloafing behavior has no effect on employee performance and organizational commitment. Meanwhile, organizational commitment has an influence on employee performance. Researchers also found that cyberloafing behavior had no effect on employee performance which was mediated by organizational commitment. Keywords: cyberloafing, employee performance, organizational commitment, internet, partial least squ